Research methods for evidence-based practice - Wodarski, John S.; Hopson, Laura M. (Los Angeles : SAGE, 2012)
'The book fully integrates evidence based practice methodology into the heart of the text, rather than in a single chapter. In addition to presenting the key concepts needed for the research methods text, the book helps students not only understand the research process, but it also equips them with the skills needed to a) evaluate studies b) translate relevant behavioral science into practice principles and implement evaluation procedures in their daily practice. The book begins with an introduction and rationale for using evidence based practice and the basic roles of an evidence based practitioner. Next the book covers evaluating research into practice generalizations. Then the authors cover designs for evaluation of practice, traditional designs, application of statistical techniques in evaluation of practice and advanced statistical techniques in social work research. Next the book covers the research process in preparing for research, developing and formulating quality proposals, developing management information systems for Human Services and emerging trends and issues'--
'The purpose of this book is to teach social work students the concepts and skills needed to apply research methods in their practice with clients. Within the last three decades, the human service professions have been challenged to base practice on empirical evidence. One promising approach to meeting this challenge is to train practitioners who can evaluate knowledge produced in the behavioral sciences and, then, translate such knowledge into practice principles. This volume aims to help practitioners under{u3D21}nd the research process and equip them with the necessary tools and skills to: (a) evaluate studies; (b) translate relevant behavioral sci$1!:s(Be knowledge into practice principles; and (c) implement evaluation procedures in their daily practice. The book also provides guidance in incorporating evidence-based practice principals and procedures into social work curricula. Evidence-based practice offers practitioners and students a method for building into the intervention process a problem-solving and evaluative component that is greatly needed in social work'--s
Includes bibliographical references and index.
Keywords: Social service -- Research; Evidence-based social work